Reappraisal of Reported Genes for Sudden Arrhythmic Death: Evidence-Based Evaluation of Gene Validity for Brugada Syndrome. Issue 12 (18th September 2018) - Hosseini, S. Mohsen; Kim, Raymond; Udupa, Sharmila; Costain, Gregory; Jobling, Rebekah; Liston, Eriskay; Jamal, Seema M.; Szybowska, Marta; Morel, Chantal F.; Bowdin, Sarah; Garcia, John; Care, Melanie; et al.
Abstract : Background: Implicit in the genetic evaluation of patients with suspected genetic diseases is the assumption that the genes evaluated are causative for the disease based on robust scientific and statistical evidence. However, in the past 20 years, considerable variability has existed in the study design and quality of evidence supporting reported gene-disease associations, raising concerns of the validity of many published disease-causing genes. Brugada syndrome (BrS) is an arrhythmia syndrome with a risk of sudden death. More than 20 genes have been reported to cause BrS and are assessed routinely on genetic testing panels in the absence of a systematic, evidence-based evaluation of the evidence supporting the causality of these genes. Methods: We evaluated the clinical validity of genes tested by diagnostic laboratories for BrS by assembling 3 gene curation teams. Using an evidence-based semiquantitative scoring system of genetic and experimental evidence for gene-disease associations, curation teams independently classified genes as demonstrating limited, moderate, strong, or definitive evidence for disease causation in BrS. The classification of curator teams was reviewed by a clinical domain expert panel that could modify the classifications based on their independent review and consensus. Results: Of 21 genes curated for clinical validity, biocurators classified only 1 gene ( SCN5A ) as definitive evidence, whereas all other genes were classified as limited evidence. After comprehensive review by the clinical domain Expert panel, all 20 genes classified as limited evidence were reclassified as disputed with regard to any assertions of disease causality for BrS. Conclusions: Our results contest the clinical validity of all but 1 gene clinically tested and reported to be associated with BrS. These findings warrant a systematic, evidence-based evaluation for reported gene-disease associations before use in patient care. Abstract : Supplemental Digital Content is available in the text.